Principles of macroeconomics (Upper Saddle River, NJ : Pearson Prentice Hall, 2004)
Contents: (1. Test Item File1/James Swofford.-- 2. Test Item File2/Paul Kasunich.-- 3.Test item File 3/Richard Gosselin.-- 4. Instructors manual/Tony Lima.)
Faculty